Continuous remission of single-mode therapy with pembrolizumab plus chemotherapy in locally advanced hypopharyngeal carcinoma: a case report - Yu, Guoning; He, Jianqiao; Gao, Yingna; Shi, Xiaoqiong; Ma, Yi; Chen, Shicai; Zheng, Hongliang; Zhu, Minhui; Zhang, Caiyun (Frontiers in Immunology, 2025)
Hypopharyngeal carcinoma, one of the common malignant tumors of the head and neck, is associated with high tumor aggressiveness, early cervical lymph node metastasis, and a poor prognosis. Neoadjuvant immunotherapy has been gradually introduced to treat locally advanced head and neck squamous cell carcinoma (LA-HNSCC), including hypopharyngeal carcinoma. Despite survival benefit advantages, there is no consensus on the treatment mode after neoadjuvant immunotherapy, especially for patients achieving a complete response (CR). It remains uncertain whether surgery, radical radiotherapy, or maintenance with immunotherapy should be chosen for patients achieving CR. Moreover, there are no reports of the successful use of monoimmunotherapy as maintenance therapy in patients who achieve CR with neoadjuvant immunotherapy. Here, we present the case of an older woman diagnosed with locally advanced hypopharyngeal carcinoma with cervical esophageal involvement who presented with dyspnea and swallowing obstruction. After 18 courses of weekly paclitaxel + carboplatin combined with cetuximab (PCC), during which she received pembrolizumab every 3 weeks, the patient’s laryngoscopy and radiologic imaging results revealed that she had achieved CR. She was subsequently maintained with pembrolizumab alone, and no tumor recurrence was observed on multiple examinations during follow-up. No surgery or radiotherapy was performed. From the beginning of treatment to the present (21 months), the patient’s general condition and quality of life improved significantly (Karnofsky performance status [KPS] = 100), and laryngeal function was well preserved. Our results indicate that patients who achieve CR after neoadjuvant immunotherapy may be maintained with immunotherapy (with surgery or radiotherapy as a salvage measure), which can improve disease-free survival in patients with relatively normal laryngeal function. This single-mode treatment may achieve long-term survival in some LA-HNSCC patients.